Effect of Charlson Comorbidity Index and Treatment Strategy on Survival of Elderly Patients After Endoscopic Submucosal Dissection for Gastric Adenocarcinoma: A Multicenter Retrospective Study - Cao, Wenzhe; Liu, Shaohua; Wang, Shasha; Wang, Shengshu; Song, Yang; He, Yao (Frontiers in Public Health, 2022)
Background: The optimal treatment strategy for elderly patients with early gastric adenocarcinoma (EGAC) after non-curative endoscopic submucosal dissection (ESD) remains unclear. The purpose of this research was to explore the effectiveness of additional treatments after ESD and the factors affecting survival in elderly patients (≥60 years of age) with EGAC. Methods: A total of 639 elderly patients (≥60 years) treated with ESD for EGAC from 2006 to 2018 were retrospectively reviewed. Positive lymphatic infiltration, submucosal infiltration, and positive/indeterminate vertical resection margins are considered high risk factors in histology. According to the risk of lymph node metastasis in patients with EAGC and the treatment strategies adopted after ESD, patients were divided into three groups: there were 484 patients in group A with low risk, 121 patients in group B with high risk, without additional treatment, and 36 patients in group C with high risk, with additional treatment. The 5- and 8-year survival rate, as well as the prognostic factors of survival rate after ESD was studied. Results: The median follow-up time was 38, 40, and 49 months, respectively. There were 3, 4, and 3 deaths related to gastric adenocarcinoma in groups A, B, and C, while deaths from other diseases were 20, 5, and 3, respectively. There were significant differences in overall survival rates between groups (94.3; 86.4; 81.2%, p = 0.110), but there was no significant difference in disease-specific survival rates (98.4; 92.7; 92.4%, p = 0.016). In the multivariate analysis, the Charlson Comorbidity Index (CCI) ≥ 2 was an independent risk factor for death after ESD (hazard ratio 2.39; 95% confidence interval 1.20–4.77; p = 0.014). Conclusions: The strategy of ESD with no subsequent additional treatment for EGAC may be a suitable option for elderly patients at high risk, especially for CCI ≥ 2.